Assessment of yeasts from winemaking environments: biosafety and functional perspectives on probiotic capabilities - Leiva Alaniz, María José; Vergara, Silvia Cristina; Mestre Furlani, María Victoria; Vazquez, Fabio; Mancha-Agresti, Pamela; Maturano, Yolanda Paola (Frontiers in Industrial Microbiology, 2025)
Probiotic yeasts are gaining significant attention due to their numerous advantages over traditional bacterial probiotics. Yeasts from winemaking environments may possess unique attributes that enhance their probiotic potential. In the present study, fourteen yeast strains were evaluated based on previous in vitro studies regarding their biosecurity and tolerance to gastrointestinal tract conditions. Biosafety was assessed using an in vivo invertebrate model, specifically Galleria mellonella, and potential in vitro properties, including enzyme production, antioxidant activity, antagonistic effects against enteropathogens, and cholesterol- lowering capabilities, were explored. Notably, all strains were deemed biosafe. Assessment of enzyme production revealed that all strains produced lipase and phytase, while six exhibited protease activity and five showed β-glucosidase activity. All isolatesdemonstrated tolerance to oxidative stress, DPPH radical scavenging (with a maximum value of 76.46%), and hydroxyl radical trapping (with a maximum value of 85.69% in Wickerhamomyces anomalus). Antimicrobial activity was also evaluated, with one strain producing siderophores. Furthermore, all strains exhibited catalase activity and produced short-chain organic acids in varying proportions, including acetic acid (with a maximum value of 1.436 g l-1 in W. anomalus), lactic acid (with a maximum value of 2.196 g l-1 in Pichia manshurica), and propionic acid (with a maximum value of 2.312 g l-1 in W. anomalus. All but one strain produced ethanol, with the highest value of 9.056 g l-1 observed in P. kudriavzevii. Importantly, all strains demonstrated the ability to reduce cholesterol levels in the medium to varying extents, with a reduction of up to 47.5% observed in P. kudriavzevii. These findings provide a robust foundation for future investigations into the potential probiotic applications of these yeasts.